Lethal recurrent mycotic ascending aortic pseudoaneurysm in a 21-month-old child with repaired subaortic membrane - Khaled A Alhawri; Usama H Elsaedy; Sami A Alahdal; Nabil S Albahlooli; Abdullah A Al Qwaee; Ali A Alakhfash (Wolters Kluwer Medknow Publications, 2020)
Mycotic pseudoaneurysm of the aorta is a rare and lethal complication of pediatric congenital heart surgery. We report the lethal consequences of recurrent mycotic pseudoaneurysm in an 18-month-old baby, early after subaortic membrane resection. We managed to repair the pseudoaneurysm successfully by replacing the infected ascending aorta using bovine jugular vein graft, but unfortunately, the patient developed new pseudoaneurysm at the site of anastomosis which led to his death. Although prompt diagnosis and surgical management can save the patient life, uncontrolled infection can lead to the recurrence of the problem and lethal results.